Pengaruh Pemasaran Dan Kualitas Produk Terhadap Keputusan Pembelian Pakaian Bekas Pada Toko Lapak Ibu Store Di Mojokerto - Irhamni, Muhammad Firdy; Nersiwad; Verlandes, Yuliasnita (PT. Kreasi Karya Majakata, 2024)
This study aims to examine the effect of marketing and product quality on purchasing decisions for used clothing at Lapak Ibu Store in Mojokerto. The population in this study were all consumers of Lapak Ibu Store in Mojokerto. The sampling technique in this study used the Accidental Sampling technique. The number of samples in this study, which were taken during the period June to July, amounted to about 100 respondents. The results of this study indicate that marketing has a positive and significant effect on purchasing decisions with a t value of 3,181 (p = 0.001) and product quality has a significant effect on choosing decisions with a t value of 8,358 (p = 0.001). Simultaneously, marketing variables and product quality together have a significant effect on purchasing decisions for used clothing at Lapak Ibu Store with an F value of 74.889> 2.665, and contribute an influence of 60.7%.